Identificação de genes diferencialmente expressos em células endoteliais obtidas pela diferenciação de células-tronco derivadas do tecido adiposo humano - Naira Roque Electo de Paiva (2011)
Stem cells were obtained from embryos and human fetuses for the first time a few years ago, giving rise to a new era in the area of development biology and its possiblemedical applications.Different strategies have been thenceforth described to obtain stem cells, among which isolation of the human&Adipose&Stem&Cell (hASC) stands out, as these have the capacity to differentiate into several mesenchymal strains, suchas endothelial cells.Nevertheless,although some phenotypic analyses can be used to prove such differentiation, in order for cellular therapy application to be safer and more efficient, genetic processes that involve stem cell differentiation into determined cellular strains still need to be completely elucidated,especially regarding differential gene expression.In this context,the objective of!this work was to identify differentially expressed genes in hASC induced! to endothelial differentiation. Stem cells were therefore extracted! from lipoaspired product, processed and evaluated by Flow Cytometry and Alkaline Phosphatase Assay. Following, VEGF and bFGF were!added to the culture medium for induction of endothelial differentiation and after 14 days, phenotypic analyses were realized through the Alkaline Phosphatase Assay, Flow Cytometry and Confocal Microscopy. In order to identify differentially expressed genes in the! cells! induced! for! differentiation,! Rapid& Subtractive& Hybridization& (RaSH) technique and posterior gene identification through sequencing and Real Time PCR were performed.The obtained results confirmed isolation of stem cells derived from the adipose tissue and endothelial differentiation after induction. Using the RaSH technique, 5 genes (ELAVL1, LAMB2, SC5DL,HARS e VEGFA)!were identified, of which VEGFA and HARS were validated through Real Time PCR with 1,5 and 1,78 times higher expression, respectively, hen compared to undifferentiated cells.